Analysis of the Influence of Marketing Mix on Purchasing Decisions for Ornamental Plants Using Chi-Square in Kendari City - Dimas Muhammad Taufiq; Agustono Slamet (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2024)
Public interest in ornamental plants continues to increase along with the trend of green lifestyle and urbanization. These changes encourage businesses to refine their marketing strategies to better attract consumers. The marketing mix, which includes elements of product, price, promotion, and place, is believed to play a significant role in influencing purchasing decisions for ornamental plants. However, the influence of each element has not been widely studied empirically in Eastern Indonesia, especially Kendari City. This study employs Chi-Square analysis to examine the impact of the marketing mix on purchasing decisions for ornamental plants. This research was conducted from January to April 2024 in Kendari City with a descriptive quantitative approach. The research sample consisted of 50 respondents selected purposively, namely consumers who had purchased ornamental plants in the last three months. The independent variables in this study include product, price, place, and promotion, while the dependent variable is the purchase decision. The analytical tool used is the Chi-Square test to determine the relationship between each element of the marketing mix and purchasing decisions. The analysis results indicate that the product and place variables are significantly related to the purchase decision for ornamental plants, whereas price and promotion do not have a significant influence. These findings provide a preliminary understanding of consumer preferences for ornamental plants in the local market, offering a basis for developing more effective and evidence-based marketing strategies in urban areas.